Cloud computing concepts and tech analogies : a guide to understand AWS services using easy to follow analogies from real life /: a guide to understand AWS services using easy to follow analogies from real life. (2023) - Prajapati, Ashish; Ruiz, Juan Carlos; Tamassia, Marco
No abstract available